Energy and Exergy Analysis for Unit13E1 of Benghazi Combined Cycle Power Plant - Elfeituri, Idris; El Gehani, Hamza (Libyan Journal for Engineering Research, 2017)
Presented in this paper, an exhaustive energy-exergy analysis of a 476 MW combined cycle power plant located in Benghazi-Libya, as an example to illustrate the utility and importance of exergy analysis compared with energy analysis. The proposed power plant cycle was simplified into sub-systems and modelled. These models of mass, energy and exergy balance equations were applied to each sub-system and farther validated by the manufacturer’s data at design operating condition. The results indicate that, the power plant has an overall energy and exergy efficiencies of 55.0% and 52.0% respectively. The total exergy destruction rate is found to be 444.2 MW (48.3 % of fuel input exergy). Significant exergy destruction rate is found to occur in the combustion chamber which contributes a major share of 340.7 MW (37.06%), followed by heat recovery steam generator with 35.7MW (4. %). Moreover, the results of the exergy analysis are compared with those of energy analysis. The comparison is quite of interest. The exergy analysis is much more enlightening, because the dissipations and efficiencies measured with availability are true one, where as those measured with energy are erroneous and misleading. The benefit of this study has enabled us to identify sites where loss of useful energy (exergy) takes place in a power plant and its performance can be evaluated. The results presented here are of real practical value in many ways, they can be valuable for the academic research interest.